2011
DOI: 10.1155/2011/786560
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Assessment and Diagnosis of Conversion Disorder in a Patient with Foreign Accent Syndrome

Abstract: Abstract. Multiple reports have described patients with disordered articulation and prosody, often following acute aphasia, dysarthria, or apraxia of speech, which results in the perception by listeners of a foreign-like accent. These features led to the term foreign accent syndrome (FAS), a speech disorder with perceptual features that suggest an indistinct, non-native speaking accent. Also correctly known as psuedoforeign accent, the speech does not typically match a specific foreign accent, but is rather a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
(51 reference statements)
0
19
0
4
Order By: Relevance
“…10,[18][19][20] Due to the variety of etiologies and lack of common features, it has been suggested that FAS is not the result of any single underlying mechanism. 7 A few cases of FAS have been reported in the literature secondary to psychogenic, rather than neurogenic causes.…”
Section: Discussionmentioning
confidence: 99%
“…10,[18][19][20] Due to the variety of etiologies and lack of common features, it has been suggested that FAS is not the result of any single underlying mechanism. 7 A few cases of FAS have been reported in the literature secondary to psychogenic, rather than neurogenic causes.…”
Section: Discussionmentioning
confidence: 99%
“…Há um relato de estudo de caso em que o sujeito apresenta um quadro de sotaque estrangeiro secundário a um transtorno de conversão 18 . Esse transtorno é definido como uma condição médica em que há a presença de sintomas ou déficits afetando a função motora ou sensorial voluntária, que sugerem uma condição neurológica ou outra condição médica geral, mas sem causas neurológicas.…”
Section: Discussionunclassified
“…En contraposición, no pudo certificarse la validez del programa de tratamiento conductual dirigido a los errores en sonidos de voz (Jones et al, 2011), por falta de sesiones, consecuencia de la petición de alta voluntaria del paciente durante el tratamiento. …”
Section: Tratamientos Del Lenguaje Aplicadosunclassified
“…Las principales etiologías que se le atribuyen al SAE, son accidentes cerebrovasculares o lesiones cerebrales traumáticas que afectan a regiones significativas en la producción del habla y del lenguaje expresivo (Jones, Story, Collins, Dejoy y Edwards, 2011). A pesar de que algunos autores como Coleman y Gurd (2006) sopesaron un origen neurogénico del SAE, a expensas de futuros estudios concluyentes, Keulen et al (2016) consideran una variante del SAE como psicógena.…”
unclassified